2006
DOI: 10.5194/angeo-24-2191-2006
|View full text |Cite
|
Sign up to set email alerts
|

IRI-2001 model predictions compared with ionospheric data observed at Brazilian low latitude stations

Abstract: Abstract. In this work, the F-region critical frequency (foF2) and peak height (hmF2) measured by digital ionosondes at two Brazilian low-latitude stations, namely Palmas The comparison at the latter station shows quite a reasonable agreement for both parameters. The former station exhibits a better agreement for hmF2 than for foF2. In general, the model generates good results, although some improvements are still necessary to implement in order to obtain better simulations for equatorial ionospheric regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 13 publications
2
34
0
Order By: Relevance
“…They showed that post sunset values of hpF2 observed at PAL presented an intense vertical drift during all the seasons. As it is well-known, there are a wide discrepancy between TEC measurements and the IRI model predictions at equatorial and low latitude regions [Bertoni et al, 2006]. The IRI-model is able to estimate well the GPS-TEC at high-and mid-latitudes, but overestimates or underestimates at low latitudes, which was previously reported by authors [Venkatesh et al, 2011;Kumar et al, 2015a].…”
Section: Variations Of Dtec (Difference Between Tec From Gps and Iri-supporting
confidence: 60%
“…They showed that post sunset values of hpF2 observed at PAL presented an intense vertical drift during all the seasons. As it is well-known, there are a wide discrepancy between TEC measurements and the IRI model predictions at equatorial and low latitude regions [Bertoni et al, 2006]. The IRI-model is able to estimate well the GPS-TEC at high-and mid-latitudes, but overestimates or underestimates at low latitudes, which was previously reported by authors [Venkatesh et al, 2011;Kumar et al, 2015a].…”
Section: Variations Of Dtec (Difference Between Tec From Gps and Iri-supporting
confidence: 60%
“…In Africa, the variations of the F 2 peak parameters obtained by the ionosonde at Ouagadougou (12.4 • N, 1.5 • S, 294.6 • E), Argentina (Batista and Abdu, 2004;Bertoni et al, 2006;Lee and Reinisch, 2006;Lee et al, 2008;Ezquer et al, 2008). In Europe, Ratovsky et al (2009) compared the observed ionospheric data with the IRI model at Irkutsk (52.3 • N, 104.3 • E), Russia.…”
Section: Introductionmentioning
confidence: 99%
“…These results differ from those obtained by , who conducted a comparative study for 6 months in 2002 by using the IRI-2001 model at a low-latitude station in Hainan and found that foF2 values are in favorable agreement during the daytime and are underestimated for the nighttime. In addition, Batista and Abdu (2004) and Bertoni et al (2006) performed similar investigations of the south EIA crest and found that the IRI model overestimates the values of foF2 at approximately 06:00 LT during April (autumn) and July (winter). Meanwhile, our results also show that the CCIR mode is slightly more effective when using the observed data than the URSI mode during the daytime in the equinox and winter.…”
Section: Discussionmentioning
confidence: 81%